Exploring the Correlation Between the Regulation of Macrophages by Regulatory T Cells and Peripheral Neuropathic Pain - Chen, Hongyu; Jiang, Liangfu; Zhang, Dupiao; Chen, Jianpeng; Luo, Xiaobin; Xie, Yutong; Han, Tao; Wang, Liang; Zhang, Zhe; Zhou, Xijie; Yan, Hede (Frontiers in Neuroscience, 2022)
Objective Intractable pain after peripheral nerve injury has become a major concern in the field of pain. Current evidence shows that routine medications or surgical treatment is associated with inconsistent results and different curative effects. Stable and effective treatment methods in clinical practice are also lacking. To date, there is no consensus on the pathophysiological mechanisms of pain. The present study investigates the potential regulatory role of regulatory T cells in the differentiation of macrophages on dorsal root ganglion (DRG) and explores the mechanism of nociceptive signals in the signal transfer station. The findings are expected to guide the prevention of various types of peripheral neuropathic pain. Methods Thirty-six male Sprague Dawley (SD) rats and 18 male Nude rats, of equal weight (250–300g), were used in this study. The rats were divided into 3 groups: SD rat sciatic nerve transection group (SNT group, n = 18), SD rat nerve transection experimental group (SNT/RAPA group, n = 18) and Nude rat nerve transection experimental group (SNT/NUDE group, n = 18). The behavior related to neuropathic pain of animals were comprehensively evaluated in all groups. Furthermore, we analyzed the degree of neuroma development, histology, gene, and protein expression, and compared their correlation with the ultrastructural changes of M1/M2 type differentiation of macrophages in DRG. Results Sciatic nerve transection (SNT), induced the aggregation of several types of macrophages in lumbar DRG of SD rats leading to a higher ratio of M1/M2. Following the inhibition of the M1 type polarization of macrophages, axon outgrowth increased significantly. A significantly lower average autotomy score was reported in the SNT/NUDE group (*p < 0.05) and the SNT/RAPA group (@p < 0.05) as compared to that of the SNT group. The SNT/NUDE group showed no noticeable neuroma formation 30 days after the nerve transection. However, bulbous neuromas were observed in the nerve stumps of both the SNT control and SNT/RAPA groups. Immunofluorescence staining revealed a significant decrease in the proportion of M1/M2 macrophages in lumbar DRG of the SNT/NUDE group (**p < 0.001) and the SNT/RAPA group (@p < 0.05) compared to the SNT group. The expression of pain-related proteins was also decreased (@p < 0.05, *p < 0.05,**p < 0.001). Also, the expression of alpha-smooth muscle actin (α-SMA), neurofilament 200 (NF-200), and nerve growth factor low-affinity receptor p75 were significantly down-regulated in the nerve tissue (@p < 0.05, @@p < 0.001, **p < 0.001). Conclusion M1/M2 type differentiation of macrophages on DRG plays a significant role in the formation of traumatic painful neuroma after neurotomy. In combination with our previous study, the results of this study suggest that regulatory T cells reduce the ratio of M1/M2 macrophages and alleviate the pain of neuroma by regulating the polarization direction of macrophages on neuroma. These findings provide key insights into developing new strategies to manage painful neuroma.